Physics - Abbott, A.F.; Foreword by Sir John Cockcroft (Melbourne Heinemann Educational Publishers, 1989)
This is the latest edition that takes into account the requirements the East African Examination Council. To reflect this, the 5th edition of Physics includes a substantial amount of new material on logic gates and their uses.
Include Illustration and Index
Keywords: Physics -- Physics--Study and teaching (Secondary)